2005
DOI: 10.1007/s10803-005-5030-2
|View full text |Cite
|
Sign up to set email alerts
|

Chronicity of Challenging Behaviours in People with Severe Intellectual Disabilities and/or Autism: A Total Population Sample

Abstract: The skills, social impairments and challenging behaviours of a total population of 166 children, with severe intellectual disabilities and/or autism, were assessed through interview with the main carers, when the children were under 15 years old (time 1). Twelve years later, 141 of these individuals were re-assessed, using the same measures (time 2). "Abnormal" behaviours tended to reduce with age and were associated with poorer language skills and poorer quality of social interaction. Individuals with most ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
128
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(142 citation statements)
references
References 50 publications
11
128
0
3
Order By: Relevance
“…9,10 Findings from the current study confirm that reported elopement is common in community settings, that children who elope face many dangers, and that elopement adds to family stress.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…9,10 Findings from the current study confirm that reported elopement is common in community settings, that children who elope face many dangers, and that elopement adds to family stress.…”
Section: Discussionsupporting
confidence: 70%
“…One study of challenging behaviors among 166 children with severe intellectual disability and/or autism found 23% and 16% experienced minor and marked wandering problems, respectively. 9 Another study of 161 severely affected adults with ASD living in an institution found 34% of those with autistic disorder (AD) and 19% of those with pervasive developmental disorder (PDD) not otherwise specified exhibited elopement behavior. 10 The objective of the current study was to provide a preliminary estimate of the reported occurrence and characteristics of elopement among children with ASD in community settings and to document factors associated with elopement.…”
Section: Introductionmentioning
confidence: 99%
“…Challenging behaviors occasioned by academic demands cause stress for parents, interfere with instruction, and impede learning (Baker et al, 2003;Cipani & Spooner, 1997;Davis & Carter, 2008;Gunter et al, 1994;Reichle, 1990;Sprague & Rian, 1993). Taken together, these factors point to a need for behavior intervention strategies that parents can use to prevent and minimize challenging behaviors and to increase appropriate responding (Matson, Boisjoli, & Mahan, 2009;Murphy et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that problem behaviour may not only have negative consequences on a child's overall development but also create significant challenges to the child's parents and other family members (McCracken et al, 2002;West & Waldrop, 2006). Given that problem behaviour is likely to persist and become chronic without appropriate intervention (Khosroshahi, Pouretemad, & Khooshabi, 2010;Murphy et al, 2005), this highlights the importance of interventions for addressing problem behaviour in children with ASD.…”
Section: Problem Behaviour In Children With Autism Spectrum Disordersmentioning
confidence: 99%